Exact and Sinusoidal Periodic Solutions of Lienard Equation Without Restoring Force - Akande, Jean; ADJAÏ, K. K. Damien; YEHOSSOU, A. V. Régis; MONSIA, MARC DELPHIN (My University, 2022)
In this paper we study a Lienard equation without restoring force. Although this equation does not satisfy the classical existence theorems, we show, for the first time, that such an equation can exhibit harmonic periodic solutions. As such the usual existence theorems are not entirely adequate and satisfactory to predict the existence of periodic solutions.
Keywords: Lienard equation; exact periodic solution; harmonic and isochronous oscillations; restoring; force; existence theorems.